ANALISIS MANAJERIAL KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN DEEP LEARNING DARI PERSPEKTIF GURU DI SMP NEGERI 1 TARUTUNG - Mei Dormauli Manullang; Pardomuan Simanullang; Baginda Sitompul (STKIP Subang, 2026)
This study aims to analyze the principal’s managerial role in implementing deep learning from the teachers’ perspective at SMP Negeri 1 Tarutung. The focus of the study includes the principal’s management functions, namely planning, organizing, supervision implementation, and learning evaluation in supporting the implementation of deep learning. This study employed a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, observations, and documentation involving informants consisting of the principal, facilitator teachers, and teachers who had participated in deep learning training. Data analysis techniques were carried out through data reduction, coding, data presentation, and thematic conclusion drawing. The results of the study indicate that the principal has a strategic role in supporting the implementation of deep learning through the preparation of learning programs, teacher organization, implementation of academic supervision, and continuous learning evaluation. The principal also strives to build a collaborative culture through training, mentoring, and strengthening communication with teachers. From the teachers’ perspective, the implementation of deep learning has a positive impact on student engagement, the development of critical thinking skills, and more meaningful learning experiences. However, its implementation still faces several challenges, such as limited teacher understanding, time management, and supporting learning facilities. Therefore, strengthening the principal’s managerial capacity, improving teacher competence, and providing continuous facilities and supervision support are necessary so that the implementation of deep learning can run optimally